A REVIEW OF "GROUP PIANO COURSE" TEXTBOOK - Milena M. Milovanović (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2015)
Group piano classes for children ages seven to nine is a new form of piano teaching in our country. Even though in our country group piano classes are not organized in public music schools, they are taught in private music schools. Group piano classes were first organized in the 19th century and today they are taught in many countries around the world. As group piano lessons are less expensive than individual lessons, more children are given the opportunity to learn how to play the piano, making these lessons an important tool in providing equal learning opportunities to all children. Ultimately, it is very important for developing countries to create good student textbooks for the overall advancement of education. In order to aid the development of group piano teaching in Serbia, this paper analyzes group piano textbooks used in other countries with the goal of finding a way of developing group piano textbooks which would be adequate for our school system. More specifically, this paper gives a review of the textbook Group piano course which was published by the Alfred publishing company, a renowned company which publishes textbooks used in the USA and in many countries around the world, including Serbia.